Word frequency effects found in free recall are rather due to Bayesian surprise - Musca, Serban C.; Chemero, Anthony (Frontiers in Psychology, 2022)
The inconsistent relation between word frequency and free recall performance (sometimes a positive one, sometimes a negative one and sometimes no relation) and the non-monotonic relation found between the two cannot all be explained by current theories. We propose a theoretical framework that can explain all extant results. Based on an ecological psychology analysis of the free recall situation in terms of environmental and informational resources available to the participants, we propose that because participants' cognitive system has been shaped by their native language, free recall performance is best understood as the end result of relational properties that preexist the experimental situation and of the way the words from the experimental list interact with those. In addition to this, we borrow from predictive coding theory the idea that the brain constantly predicts "what is coming next" so that it is mainly prediction errors that will propagate information forward. Our ecological psychology analysis indicates there will be "prediction errors" because the word frequency distribution in an experimental word list is inevitably different from the particular Zipf's law distribution of the words in the language that shaped participants' brains. We further propose the particular distributional discrepancies inherent to a given word list will trigger, as a function of the words that are included in the list, their order, and of the words that are absent from the list, a surprisal signal in the brain, something that is isomorphic to the concept of Bayesian surprise. The precise moment when Bayesian surprise is triggered will determine to what word of the list that Bayesian surprise will be associated, and the word the Bayesian surprise will be associated with will benefit from it and become more memorable as a direct function of the magnitude of the surprisal. Two experiments are presented that show a proxy of Bayesian surprise explains the free recall performance and that no effect of word frequency is found above and beyond the effect of that proxy variable. We then discus how our view can account for all data extant in the literature on the effect of word frequency on free recall.